2021
DOI: 10.1016/s2665-9913(21)00186-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 mRNA vaccine in patients with rheumatoid arthritis

Abstract: Anti-SARS-CoV-2 mRNA vaccine in patients with rheumatoid arthritisLong-term vaccine-induced immunity is crucial for controlling the COVID-19 pandemic. Vaccination against COVID-19 is recommended for patients with rheumatic diseases, but a paucity of data are available regarding COVID-19 vaccines in patients with rheumatoid arthritis. Because patients receiving immunosuppressive treatment were excluded from the phase 3 clinical trials, 1,2 it is not clear whether disease-modifying anti-rheumatic drug (DMARD) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 7 publications
3
44
0
2
Order By: Relevance
“…Out of this, data from 25 studies was used for analysis. Table 1 provides the details of the included studies including site of the study, numbers vaccinated in IMIDs, underlying disease and drugs, the number and type of vaccine received [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. Supplementary Table 2 lists the reasons for exclusion of studies [ [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of this, data from 25 studies was used for analysis. Table 1 provides the details of the included studies including site of the study, numbers vaccinated in IMIDs, underlying disease and drugs, the number and type of vaccine received [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. Supplementary Table 2 lists the reasons for exclusion of studies [ [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ].…”
Section: Resultsmentioning
confidence: 99%
“… Antibodies against RBD were determined after second vaccination Response (29/74) IgG4-related (1/2) Connective tissue diseases (5/22), RA (13/33), Vasculitis (10/17). Control (10/10) Any csDMARD (16/42) MTX (10/24), MMF (2/8), HCQ (3/7, AZA (1/5), Leflunomide (2/4) SAAZ (1/1) Prednisone (8/22) Deepak P et al [ 27 ] (USA) 133 chronic inflammatory diseases 53 controls mean age 45.5 ± 16.0 years, Females ( n = 99) mRNA second dose IBD ( n = 43), Inflammatory arthritis (n = 2), RA ( n = 35), SpA (n = 6), SLE ( n = 13), Sjogren (n = 2), Psoriasis (n = 2), PsA (n = 5) anti-S IgG quantification was performed using ELISA and direct ex-vivo ELISpot assays were performed to quantify recombinant S protein-binding IgG secreting cells 96% of blood samples collected within 14 days post-vaccination Response (117/133), IBD (42/43), Inflammatory arthritis (2/2), RA (30/35), SpA (5/6), SLE (12/13), Sjogren (2/2), Psoriasis (1/2), PsA (5/5) Response in control (52/53) AZA (4/4), MMF (7/9), MTX (26/29), Leflunomide (2/2), Steroid (10/17), TNFi (35/38), Infliximab (6/6), Adalimumab (13/14), Golimumab (2/2), Abatacept (1/2), Vedolizumab (12/12), Ustekinumab (9/9), anti-IL 12/21 (10/10), Tofacitinib (10/10), Rituximab (5/6), anti- IL6(1/1), Rubbert-Roth et al [ 28 ] (Switzerland) 51 RA mean age 64·6 (11·5) years, Females ( n = 29) mRNA First dose second dose RA ( n = 51) Roche Elecsys Anti-SARS-CoV-2 spike subunit 1 (S1) A lower cutoff level of >15 U/mL has been suggested, emphasising the need to establish formal cutoff levels of anti-SARS-CoV-2 antibody titres associated with protection against SARS-CoV-2 infection and severe disease. Response in first dose (5/51), Second dose (45/51), RA (45/51) Control (20/20) csDMARD (13/16), MTX (24/28), Steroid (16/17), Biologicals (9/9), Abatacept(4/5), JAKi (4/5), Ruddy et al [ 29 ] (USA) ...…”
Section: Resultsmentioning
confidence: 99%
“… 3 , 4 Lower seroconversion rates than in healthy controls have been reported in patients with rheumatic diseases receiving immunomodulatory therapies. 5 , 6 …”
mentioning
confidence: 99%
“…We read with interest the Article by Andrea Rubbert-Roth and colleagues, 1 which reported that among 53 patients with rheumatoid arthritis on various biological, conventional synthetic, and targeted synthetic disease-modifying anti-rheumatic drugs (DMARDs), antibody responses to COVID-19 vaccination was reduced compared with healthy controls.…”
mentioning
confidence: 99%